Renewal of the city network in Szabolcs-Szatmár-Bereg country after the political restructuring - Deák, Attila (Acta Agraria Debreceniensis, 2012)
After World War I., but especially from the second half of the 20th century the public policy development is determinative in urban development. The urban and the country planning appears under the auspices of the regional development policy between the world wars. After 1945 the primary goal in economic and development policy was the socialist industrialization, with a priority on cities. In this period the driving force in urban development primarily were the industrial installations. As a result, economic and social structure was transformed. It is a fact, that planned economy gave a huge impulse to city network, which determine the trend of cities up to this day. After the regime change, as an effect of escalation of regional differences and as a result of economic processes the urban development took new directions. The state intervention changed, and the principles of decentralization prevailed in resource allocation. The private and non-profit sector appears in urban development, the governments gain more important roles. These three sectors became the movers of local development. To recognize the main trends of urban development in Szabolcs-Szatmár-Bereg County, the local area development funds were examined in a special way in a given period. This study will show, the main tendencies of the consumption of decentralized regional development funds between 1996–2008, in the cities of Szabolcs-Szatmár-Bereg County. This study also gives an answer for which factors convert the renewal of city network of Szabolcs-Szatmár-Bereg County after the regime change.